(untitled) (Journal of Economic Research & Business Administration, 2015)
Obviously, there is a direct relationship between investment attractiveness and the amount of resources available to the public limited company. Since the number of resources is limited, companies in the competition for these resources must increase their own investment attractiveness. But the use of debt and equity sources requires certain costs, so to achieve the most efficient use of capital company must constantly vary the ratio of debt and equity. Then as a consequence of a competent investment the company’s value must grow. It is from this perspective, the article discusses the process of formation of financial capital structure. Also is studied the possibility of influence on investment attractiveness through the formation of the most effective capital structure. In the process criteria of optimization are considered as well as capital, classification and brief description of the methods of optimization of capital.